Penetapan Harga Jasa Angkut Gerobak Pelabuhan Sanana: Perspektif Hukum Ekonomi Syariah - Erina Junaidi; Damarina Liambana (Al-Mizan: Jurnal Kajian Hukum dan Ekonomi, 2025)
The operational reality of cart transport services at Sanana Port is frequently plagued by unclear pricing mechanisms and rate fluctuations that trigger unfairness, despite their vital role in North Maluku’s logistics. This study critically examines these issues through the lens of Sharia Economic Law to formulate equitable transaction standards. Utilizing a normative-juridical qualitative method, the research reveals that the prevailing informal bargaining system potentially violates sharia principles due to inherent uncertainty (gharar) and the exploitation of bargaining power. From the perspective of the ijarah 'ala al-a'mal contract, transaction validity strictly requires wage transparency (ujrah) calculated based on objective indicators such as cargo volume and travel distance, rather than subjective estimation. The findings strongly recommend implementing the concept of ta'sir, or government price intervention, to establish reasonable rate limits. This regulation is crucial for protecting weaker parties, preventing monopoly, and ensuring public good (maslahah). Ultimately, synergy between rate standardization and strict supervision is expected to create a harmonious, transparent port ecosystem that ensures prosperity for all stakeholders.